2016
DOI: 10.17352/jvi.000016
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Recombinant Genotype VII Vaccine against Challenge with Velogenic Newcastle Disease Virus

Abstract: Background: Newcastle disease virus (NDV) genotype VII has become the dominant genotype in China. However, NDV genotype II was used to make current commercial NDV vaccines. The mismatch of genotypes between circulating and vaccine strains of viruses may compromise the efficacy of vaccines. Methods:In this study, a current circulating NDV was attenuated by mutations of multiple basic amino acid motif of fusion cleavage site 112 RRQKGF 117 based on reverse genetic techniques. The recombinant virus was prepared a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Therefore, the experimentally prepared NDV vaccine induce the highest protective HI titers and enabled the challenged birds to exhibit better clinical protection and optimum efficacy against mortality. These results are harmonized with the recently reported by (Cheng et al, 2016;Mahmoud et al, 2019;Bello et al, 2020). Conversely, Adi et al (2019) found lower antibody titers induced by genotype VII NDV vaccines than of commercial genotype II, although it could fully protect chickens.…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 89%
“…Therefore, the experimentally prepared NDV vaccine induce the highest protective HI titers and enabled the challenged birds to exhibit better clinical protection and optimum efficacy against mortality. These results are harmonized with the recently reported by (Cheng et al, 2016;Mahmoud et al, 2019;Bello et al, 2020). Conversely, Adi et al (2019) found lower antibody titers induced by genotype VII NDV vaccines than of commercial genotype II, although it could fully protect chickens.…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 89%
“…To prevent virus shedding and infection more than 6log 2 of antibody titers must be obtained (Kapczynski and King, 2005;Raghul et al, 2006;Han et al, 2017). Consequently, the attenuated virus was a potent inducer of an ascending titer of anti-hemagglutinin antibodies just 1 WPV (7 log2) in correlation with a high protection level in preventing mortalities and clinical manifestations and was consistent with earlier studies (Cheng et al, 2016;Bello et al, 2020).…”
Section: Reduction Of Virus Shedding and Histopathological Lesionssupporting
confidence: 85%
“…The antigenic differences in neutralizing epitopes between the circulating virulent viruses (e.g., genotype VII.1.1) and the vaccine strains may be responsible for the inadequate vaccine efficacy [4,13,15,16]. Furthermore, the higher matching percent of aa in the F and HN proteins of NDV vaccines and the field virus is essential for enhancing vaccine protection in terms of reduced infectivity and minimized viral shedding rate [6,14,15,[17][18][19][46][47][48]. Previously, high protection and a reduction in viral shedding have been reported in birds vaccinated with recombinant vaccines containing genotype I (D26) and challenged by heterologous genotypes VII.1.1, VII.2, and V of NDV [49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%